Drones - Abell, Tracy; Roumanis, Alexis (21st century technology., 2019)
Explores the technology behind drones highlighting potential concerns and how they might be utilized in the future. Includes a text-related quiz with an answer key, a glossary, color photographs, and access to further online resources.